Rizatriptan for acute migraine - Oldman, Anna (Cochrane Database Syst Rev, 2001)
This review was withdrawn at the request of the Cochrane funding arbitration panel. There was no suggestion that the results of the review were mistaken, and it has been confirmed by other, subsequent, systematic reviews by other authors. The review fulfilled the criteria required by The Cochrane Collaboration at the time of submission, and the source, nature, and terms of funding were discussed openly and fully. This funding included an absolute right to publish for the authors, with no interference from the funding source. This review has now been replaced by a new published protocol: Ling R, Derry S, Moore RA, McQuay HJ, Wiffen PJ. Rizatriptan for acute migraine headaches in adults (Protocol). Cochrane Database of Systematic Reviews 2010, Issue 4. Art. No.: CD008491. DOI: 10.1002/14651858.CD008491. The editorial group responsible for this previously published document have withdrawn it from publication.